Physical Therapists Diagnosing Musculoskeletal Conditions: Don’t Hide What Matters—Just Say It the Right Way - Marc Perron; Jean-Sébastien Roy; Hugo Massé-Alarie; Luc J. Hébert (Journal of Orthopaedic & Sports Physical Therapy, 2026)
SYNOPSIS: Recently, the use of nonpathoanatomical functional diagnoses has been advocated as a way of reducing patients’ psychological distress and limiting the use of low-value interventions aimed at “fixing” perceived causes of pain and disability. However, we argue that not disclosing a pathoanatomical diagnosis may withhold essential information that patients need to fully understand their prognosis and treatment plan, as well as appropriate precautions and contraindications. The way clinicians communicate a pathoanatomical diagnosis can mitigate its potential drawbacks while also supporting patients in making sense of what is happening in their body. J Orthop Sports Phys Ther 2026;56(9):566-568. Epub 3 June 2026. doi:10.2519/jospt.2026.14197